2004
DOI: 10.1002/ajh.20045
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T‐lymphocyte antigen‐4 (CTLA‐4) gene polymorphism and susceptibility to non‐Hodgkin's lymphoma

Abstract: The CTLA-4 molecule plays an important role in immune regulation by downregulating activation of T cells. Polymorphisms in the CTLA-4 gene have been shown to be associated to a number of autoimmune diseases including blood disorders. In this study, the intragenic polymorphisms of the CTLA-4 gene at position -318*C/T, +49*A/G, and the dinucleotide (AT) n repeat polymorphism in exon 3 were analyzed in patients with nonHodgkin's lymphoma. Genotype and haplotype analysis showed that the exon 1+49*AA genotype was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 25 publications
1
46
0
3
Order By: Relevance
“…Sun et al found it to be associated with the cancer of oesophagus and lung among the Chinese (Sun et al, 2008) and an association with gastric cancer was found by Hou et al (Hou et al, 2010). It has also been associated with non-solid tumours like non-Hodgkin's lymphoma (Monne et al, 2004). Another study found this SNP to be associated with bad lung cancer prognosis (Song et al, 2011).…”
Section: 2035 Lack Of Any Association Of the Ctla-4 +49 G/a Polymorpmentioning
confidence: 98%
“…Sun et al found it to be associated with the cancer of oesophagus and lung among the Chinese (Sun et al, 2008) and an association with gastric cancer was found by Hou et al (Hou et al, 2010). It has also been associated with non-solid tumours like non-Hodgkin's lymphoma (Monne et al, 2004). Another study found this SNP to be associated with bad lung cancer prognosis (Song et al, 2011).…”
Section: 2035 Lack Of Any Association Of the Ctla-4 +49 G/a Polymorpmentioning
confidence: 98%
“…It has been demonstrated that variations in the promoter region are likely to affect gene expression. The -318C/T (rs5742909) SNP is located in the promoter region of the CTLA-4 gene (34), and it has been suggested that this variation affects promoter activity and therefore the expression of CTLA-4 on the cell surface (35). Carriers of the T allele showed a marked enhancement of CTLA-4 mRNA expression and consequently, more expression of CTLA-4 protein on the cell surface (7).…”
Section: Snpmentioning
confidence: 99%
“…The results of the study conducted by Lieu et al 6 showed that rs231775 polymorphism of CTLA-4 was associated with osteosarcoma risk (GG vs Allele A and genotype AA of the CTLA-4 gene+49A/G polymorphism were defined as the risk factors for cancer. The findings of Monne et al 19 indicate that the genotype and haplotype analysis showed the exon 1+49 AA genotype was over-represented among patients with Non-Hodgkin's Lymphoma (NHL). Farbod et al 8 investigated the potential influences of cytotoxic T-lymphocyte antigen-4 (CTLA-4) gene polymorphisms on breast cancer risk, the distribution of CTLA-4 single nucleotide polymorphisms (1661AG) in breast cancer patients and controls.…”
Section: Discussionmentioning
confidence: 99%